Lexical Diversity, Lexical Sophistication, and Predictability for Speech in Multiple Listening Conditions - Baese-Berk, Melissa M.; Drake, Shiloh; Foster, Kurtis; Lee, Dae-yong; Staggs, Cecelia; Wright, Jonathan M. (Frontiers in Psychology, 2021)
When talkers anticipate that a listener may have difficulty understanding their speech, they adopt a speaking style typically described as “clear speech.” This speaking style includes a variety of acoustic modifications and has perceptual benefits for listeners. In the present study, we examine whether clear speaking styles also include modulation of lexical items selected and produced during naturalistic conversations. Our results demonstrate that talkers do, indeed, modulate their lexical selection, as measured by a variety of lexical diversity and lexical sophistication indices. Further, the results demonstrate that clear speech is not a monolithic construct. Talkers modulate their speech differently depending on the communication situation. We suggest that clear speech should be conceptualized as a set of speaking styles, in which talkers take the listener and communication situation into consideration.